5-Azacytidine Inhibits the Activation of Senescence Program and Promotes Cytotoxic Autophagy during Trdmt1-Mediated Oxidative Stress Response in Insulinoma β-TC-6 Cells - Kamila Filip; Anna Lewińska; Jagoda Adamczyk-Grochala; Antonella Marino Gammazza; Francesco Cappello; Marianna Lauricella; Maciej Wnuk (Cells, 2022)
5-Azacytidine (5-azaC), a methyltransferase inhibitor and anticancer drug, can promote several cellular stress responses such as apoptosis, autophagy, and senescence. The action of 5-azaC is complex and can be modulated by dose, time of treatment, and co-administration with oxidants. Insulinoma is a rare pancreatic neuroendocrine tumor with limited chemotherapeutic options. In the present study, two cellular models of insulinoma were considered, namely NIT-1 and β-TC-6 mouse cells, to evaluate the effects of 5-azaC post-treatment during hydrogen peroxide-induced oxidative stress. 5-azaC attenuated the development of oxidant-induced senescent phenotype in both cell lines. No pro-apoptotic action of 5-azaC was observed in cells treated with the oxidant. On the contrary, 5-azaC stimulated an autophagic response, as demonstrated by the increase in phosphorylated eIF2α and elevated pools of autophagic marker LC3B in oxidant-treated β-TC-6 cells. Notably, autophagy resulted in increased necrotic cell death in β-TC-6 cells with higher levels of nitric oxide compared to less affected NIT-1 cells. In addition, 5-azaC increased levels of RNA methyltransferase Trdmt1, but lowered 5-mC and m6A levels, suggesting Trdmt1 inhibition. We postulate that the 5-azaC anticancer action may be potentiated during oxidative stress conditions that can be used to sensitize cancer cells, at least insulinoma cells, with limited drug responsiveness.